Effect of heavy ion beam irradiation on germination of local Toraja rice seed (M1-M2) mutant generation. (May 2018) - Sjahril, R; Riadi, M; Rafiuddin,; Sato, T; Toriyama, K; Abe, T; Trisnawaty, A R
Abstract: Local rice in general has several weaknesses among others, long life, high plant posture and low yield result. The character is a limiting factor that causes farmers low interest to grow local rice. It is feared this will cause the lack of local rice cultivars as germplasm materials. Therefore, there is an effort to create a diversity of morphological characters, as the character of selection, especially related to the age of harvest and plant posture. One method is through breeding mutation by irradiation using ion beam. The objective of this research is to evaluate seed germination resulted after irradiation using ion beam in two varieties of Toraja local rice. The study was prepared based on a randomized block design pattern consisting of six treatments by testing two local Toraja rice varieties namely Pare Ambok and Pare Lea treated with ion beam irradiation of Argon and Carbon ion and control plant as comparison. Each grain from one panicle was germinated in one line method on a Ø15 cm Petri dish and transplanted into small plastic bags. Each treatment was repeated as much as 20 times which was then considered as a strain. The results showed that irradiation using Argon ion in local rice seed of Pare Ambok variety and of Pare Lea varieties produce better seedlings sprouts than irradiation using Carbon ion. Further M2 seed germination shows uniqueness in some seedlings produced such as lighter leaf color, albinism, wrinkled leaf, etc. which could prove potential mutant lines in tested M2 lines seed.